2011
DOI: 10.1111/j.1471-0528.2011.03175.x
|View full text |Cite
|
Sign up to set email alerts
|

Practical simulation training for maternity care—where we are and where next

Abstract: Improving maternal and perinatal care is a global priority. Practical simulation training for maternity care might prevent many of these deaths. There have been numerous evaluation studies published on the effectiveness of simulation training for obstetric emergencies, with increasing evidence that it is associated with improvement in clinical outcomes. Evidence has begun to move from subjective assessment of participants' experiences towards objective assessment of clinical outcomes. However, the results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 44 publications
0
36
0
5
Order By: Relevance
“…Other studies in low-resource settings have also found that provider simulation-based training can positively impact maternal and/or neonatal health outcomes 34,35. For example, the Helping Babies Breath curriculum in Tanzania, which uses low-fidelity simulations, found a significant decrease in early neonatal mortality after training in neonatal resuscitation 14. To date, however, PRONTO training represents the only evaluated and operational training program that combines high-fidelity in-situ simulation, interprofessional team-training, and care of the maternal-neonatal dyad in resource-limited settings.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies in low-resource settings have also found that provider simulation-based training can positively impact maternal and/or neonatal health outcomes 34,35. For example, the Helping Babies Breath curriculum in Tanzania, which uses low-fidelity simulations, found a significant decrease in early neonatal mortality after training in neonatal resuscitation 14. To date, however, PRONTO training represents the only evaluated and operational training program that combines high-fidelity in-situ simulation, interprofessional team-training, and care of the maternal-neonatal dyad in resource-limited settings.…”
Section: Discussionmentioning
confidence: 98%
“…Continued clinical training is an important element of quality improvement, and simulation-based training in particular is an effective strategy for training teams to respond to obstetric and neonatal emergencies 12,14,15. Simulation-based obstetric emergency trainings emphasizing teamwork and communication have demonstrated improved provider confidence and competence as well as patient outcomes in resource-stable countries 1618.…”
mentioning
confidence: 99%
“…In addition, the program used simulation-based learning; EmONC training emphasizing a simulation-based learning approach has been found to enhance practice [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…One of the potential difficulties in providing education at local level can be a lack of local expertise in the provision of this type of training . Provision of expert teachers is a prerequisite for successful training and for the provision of appropriate feedback following the training scenarios.…”
Section: Discussionmentioning
confidence: 99%